The effect of the COVID-19 pandemic on primary care physicians in Israel, with comparison to an international cohort: a cross-sectional study - Limor Adler; Shlomo Vinker; Anthony D. Heymann; Esther Van Poel; Sara Willems; Galia Zacay (BMC, 2022)
Abstract Background The COVID-19 pandemic had a major impact on primary care and primary care physicians (PCPs) in Israel and around the world. There is paucity of information regarding treatment of patients with COVID-19 in the community, since most research was performed in hospitals. The aim of this study was to describe the Israeli PCPs' experience. Methods This study is a part of an international cross-sectional study, the PRICOV-19. A translated version of the questionnaire was distributed among Israeli PCPs from December 2020 to July 2021. In this study, we describe the Israeli results and compare them to the international results. Results 5,961 respondents from 29 countries answered the questionnaire, 94 from Israel, with an Israeli response rate of 16%. Israeli PCPs reported an increase in use of telemedicine from 11 to 49% during the COVID epidemic. PCPs also reported a decline in their wellbeing; absence of secured time slots for keeping updated; perception that the Ministry of Health guidelines were a threat to the staff wellbeing and organization of practice and delays in the examination of non-COVID urgent cases. Conclusions The findings of this study raise concerns regarding the PCPs experience and may form the basis for an improved process of care. Guidelines for proper usage of telemedicine, substitutes for the physical examination and procedures for minimizing delayed patient examination for urgent conditions should be developed. Government directives and clinical guidelines should be communicated in a timely manner, with secured timeslots for physicians' self-learning or updating. Ensuring physicians' well-being in general should be an organization priority.